Ordovician metagranites and migmatites of the Svratka and Orlice-Sneznik Units, northeastern Bohemian Massif - Burianek,D.; Verner,K.; Hanzl,P.; Krumlova,H. (Journal of Geosciences, 2009)
Metagranites and migmatites of the Svratka and the Orlice-Sneznik units, northeastern Bohemian Massif, exhibit a number of similarities in their lithological, mineralogical and geochemical features. Both of these units were affected by intense migmatitization accompanied by intrusion of peraluminous granites during the Cambrian to Ordovician. The chemical composition and mineralogy of all the studied rocks correspond to crustal melts. From the geochemical point of view, both rock groups (migmatites and metagranites) exhibit progressive geochemical fractionation (increase in the SiO2, Rb, XFeO, W and Sn contents, accompanied by a decrease in the concentrations of Ba, Sr, Mg and Ca) as a result of varying degrees of partial melting and fractional crystallization. The main rock-forming minerals are influenced by metamorphic recrystallization under amphibolite-facies conditions during the Variscan orogeny.
Keywords: Bohemian Massif; Cambro-Ordovician rifting; geochemistry; metagranite; migmatite; microstructures; Variscan orogeny